Three New Diketopiperazines from the Previously Uncultivable Marine Bacterium Gallaecimonas mangrovi HK‐28 Cultivated by iChip. Issue 7 (23rd June 2020) - Ding, Lijian; Xu, Peng; Zhang, Weiyan; Yuan, Ye; He, Xiaoping; Su, Dengquan; Shi, Yutong; Naman, C. Benjamin; Yan, Xiaojun; Wu, Bin; Lazaro, J. Enrico H.; Li, Shengying; et al.
Abstract: The in situ application of iChip cultivation in mangrove sediment from Hainan province, China, led to the isolation of a novel bacterial species Gallaecimonas mangrovi HK‐28. The extract of G. mangrovi HK‐28 exhibited antibiotic activity against the aquatic pathogen Vibrio harveyi, and its chemical constituents were further investigated by bioactivity‐guided isolation. Three new diketopiperazines, gallaecimonamides A–C, were accordingly isolated from the AcOEt extract of the fermentation broth of G. mangrovi HK‐28. The planar structures of gallaecimonamides A–C were determined using HR‐ESI‐MS together with 1D‐ and 2D‐NMR. The absolute configurations of gallaecimonamides A–C were assigned by optical rotation, NOESY experiment and TDDFT ECD calculations. The in vitro antibacterial and antimalarial activities of gallaecimonamides A–C were assessed. Gallaecimonamide A was found to display antibacterial activity against V. harveyi with a MIC value of 50 μm . However, gallaecimonamides B and C showed no antibacterial activity against V. harveyi (MIC >300 μm ). In addition, all the isolates did not exhibit any inhibitory activities against V. parahaemolyticus (MIC>300 μm ) and Plasmodium falciparum W2 (EC50 >100 μg/mL). Abstract :